Determinants of Irritant Contact Dermatitis Symptoms Among Waste Collectors in Pasar Raya Padang - R.Firwandri Marza; Vitratul Ilahi (CV. Get Press Indonesia, 2026)
Irritant contact dermatitis is one of the most common occupational skin disorders among informal sector workers, including waste collectors who are routinely exposed to irritant materials. This study aimed to analyze factors associated with irritant contact dermatitis symptoms among waste collectors in Pasar Raya Padang. An analytical observational study with a cross-sectional design was conducted involving 75 respondents selected using a total sampling technique. Independent variables included duration of exposure, length of employment, personal hygiene, and use of personal protective equipment (PPE). Data were collected using structured questionnaires and direct observation, then analyzed using the chi-square test with a significance level of 0.05 and presented as odds ratios (OR). The results showed that 58.7% of respondents experienced dermatitis symptoms. Significant associations were found between length of employment (p=0.021; OR=3.10) and PPE use (p=0.013; OR=3.85) with dermatitis symptoms. Meanwhile, duration of exposure (p=0.642; OR=1.28) and personal hygiene (p=0.274; OR=1.54) were not significantly associated. Waste collectors with longer working periods and non-compliance with PPE use had a higher risk of experiencing dermatitis symptoms. In conclusion, length of employment and PPE use were significant factors associated with irritant contact dermatitis symptoms among waste collectors. Strengthening PPE compliance and occupational health education are recommended to reduce the risk of occupational skin disorders in informal sector workers.